Exploring pregnancy termination experiences and needs among Malaysian women: a qualitative study - Tong, W.T.; Low, W.Y.; Wong, Y.L.; Choong, S.P.; Jegasothy, R. (2012)
Background: Malaysia has relatively liberal abortion laws in that they permit abortions for both physical and mental health cases. However, abortion remains a taboo subject. The stagnating contraceptive prevalence rate combined with the plunging fertility rate suggests that abortion might be occurring clandestinely. This qualitative study aimed to explore the experiences of women and their needs with regard to abortion. Methods: Women from diverse backgrounds were purposively selected from an urban family planning clinic in Penang, Malaysia based on inclusion criteria of being aged 21 and above and having experienced an induced abortion. A semi-structured interview guide consisting of open ended questions eliciting women's experiences and needs with regard to abortion were utilized to facilitate the interviews. Audio recordings were transcribed verbatim and analyzed thematically. Results: Thirty-one women, with ages ranging from 21-43 years (mean 30.16 +/- 6.41), who had induced surgical/medical abortions were recruited from an urban family planning clinic. Ten women reported only to have had one previous abortion while the remaining had multiple abortions ranging from 2-8 times. The findings revealed that although women had abortions, nevertheless they faced problems in seeking for abortion information and services. They also had fears about the consequences and side effects of abortion and wish to receive more information on abortion. Women with post-abortion feelings ranged from no feelings to not wanting to think about the abortion, relief, feeling of sadness and loss. Abortion decisions were primarily theirs but would seek partner/husband's agreement. In terms of the women's needs for abortion, or if they wished for more information on abortion, pre and post abortion counseling and post-abortion follow up. Conclusions: The existing abortion laws in Malaysia should enable the government to provide abortion services within the law. Unfortunately, the study findings show that this is generally not so, most probably due to social stigma. There is an urgent need for the government to review its responsibility in providing accessible abortion services within the scope of the law and to look into the regulatory requirements for such services in Malaysia. This study also highlighted the need for educational efforts to make women aware of their reproductive rights and also to increase their reproductive knowledge pertaining to abortion. Besides the government, public education on abortion may also be improved by efforts from abortion providers, advocacy groups and related NGOs.